Rancang Bangun Sistem Absensi Peserta Magang Di PT Pegadaian Kanwil I Medan Berbasis Web - Ginting, Riah Ukur; Santi Dwi Marni Telaumbanua; Dini M Hutagalung; Burhanuddin Damanik (Universitas Sari Mutiara Indonesia, 2024)
Attendance is an activity used to measure a person's level of discipline in an organization or company. Currently, several companies or organizations are starting to implement manual work attendance systems inside and outside the office. One example is that the author uses attendance at PT Pegadaian Kanwil I Medan for interns using Google Forms for activities inside and outside the office. This research method uses waterfall, the PHP programming language, and MySQL. The aim of this research is to build an information system for intern attendance at PT Pegadaian Kanwil I Medan effectively and efficiently using a web-based Global Positioning System (GPS). The results of this research can help and make it easier for interns at PT Pegadaian Kanwil I Medan to carry out attendance accurately and provide attendance report data for interns at PT Pegadaian Kanwil I Medan.